Les limites de la cartographie des risques littoraux : des perspectives pour la compréhension de tous - Aurélie Arnaud (VertigO)
Maps is considered as an image allowing a "global and instantaneous reading" of information (Levy, 2002) due to use figurative and symbolic language. Maps offers the ability to read plurality representations of space. If its widespread medium is paper, screens (computers, tablets and phones) are becoming preferred visualization interfaces. They are accompanied by two crucial technological contributions: GIS software (Geography Information System) and ICT (Information and Communication Technologies) whose web technology. These advents enabled map to grow and become a real communication and decision support tool, facilitating the observation and analysis of phenomena - interactions between processes of human organization with his non-human environment - on space and in time. This digital age associated embedded devices (cell) are transforming both "map factory" by / for scientists, but also its access to public and decision makers. However, the emergence of this new cartography should not forget the basic construction rules and methods to represent information correct dimensions depending on the end user and reduce / eliminate designer subjectivity. In 2010, Xynthia storm (western France) marks development of a large cartographic production highly contested (Mercier et al, 2012), imposing a re-questioning of process of construct maps. Xynthia also shows that mapping embodies technical able to be violated to serve individuals goal ant not common interests. To ameliorate the understanding of these phenomena, we explain construct map process applied to coastal risk. These are important issues - especially related to tourism and marine economy - are subjected to increasing hazards (frequency of storms, rising sea levels, etc.). Moreover, coastal communities have the highest number of natural disaster order - Catnat (ONRS, 2011 and BD GASPAR). With this in mind we emit some recommendations in the adaptation maps areas to end users. It has a major stake in the decision making to local actors and public communication (locals as tourists).